2003
DOI: 10.1046/j.1360-0443.2003.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of snus (oral moist snuff ) in smoking cessation and smoking reduction in Sweden

Abstract: AimsTo assess to what extent snus has been used as an aid to stop smoking among Swedish smokers. Design A random telephone retrospective survey of Swedish smokers and ex-smokers. Setting Survey conducted in November-December 2000. Participants A national sample of 1000 former and 985 current daily smokers aged 25-55 years. Measurements Smoking status, date and method of quitting by self-report. Findings Thirty-three per cent of former smokers and 27% of current smokers had ever used snus . The difference was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
89
1
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 21 publications
11
89
1
6
Order By: Relevance
“…However, since individuals who combine smoking with snus use may be exposed to a lower smoking dose and may increase their overall chances of subsequent abstinence compared to those who only smoke, 21 residual negative confounding from total cumulative smoking dose is an important concern. Indeed, while a Swedish case-control study found no significant relation between use of snus and overall risk of head and neck cancer, snus use among never-smokers (where this residual confounding is more likely to have been eliminated) was associated with an increased risk of 4.7 (95% CI 1.6-13.8).…”
Section: Discussionmentioning
confidence: 99%
“…However, since individuals who combine smoking with snus use may be exposed to a lower smoking dose and may increase their overall chances of subsequent abstinence compared to those who only smoke, 21 residual negative confounding from total cumulative smoking dose is an important concern. Indeed, while a Swedish case-control study found no significant relation between use of snus and overall risk of head and neck cancer, snus use among never-smokers (where this residual confounding is more likely to have been eliminated) was associated with an increased risk of 4.7 (95% CI 1.6-13.8).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2009) found no advantage in cessation for men who switched to smokeless tobacco. However, several studies conducted in Sweden, where use of snus is relatively common among men, have concluded that males who use snus have greater odds of quitting cigarette smoking than those who do not use snus (Furberg et al, 2005;Gilljam & Galanti, 2003;Ramström & Foulds, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the delivery speed is slower in snus use, the strength of nicotine dependence could be assumed to decrease [10]. Indeed, a substantial number of switchers eventually quit snus use as well and become tobacco-and nicotine-free [3,4].…”
mentioning
confidence: 99%
“…In this context there has been a good deal of discussion regarding the effectiveness of snus, the Swedish type of low-toxicity smokeless tobacco. In Sweden this product has been used extensively for smoking cessation and a high degree of effectiveness has been demonstrated, both for men and women [3][4][5].…”
mentioning
confidence: 99%